A Constructivist Approach to Manage Business Process as a Dynamic Capability. (5th February 2014) - Lacerda, Rogerio Tadeu de Oliveira; Ensslin, Leonardo; Ensslin, Sandra Rolim; Dutra, Ademar
<x xml:space="preserve">Abstract</x> This paper proposes a constructivist methodology of business process management to aid managers to generate understanding of the environment of their organization and to build recommendations on their resources and capabilities to create competitive advantages. This research is characterized as an applied research, and it is used a study case to illustrate how the use of presented framework may aid decisions to manage business processes as a dynamic capability. The presented framework is called Business Process Management—Constructivist. The presented framework is an extension of a performance measurement methodology and provides procedures to expand the understanding of the decision‐maker about specific context and to recognize the uniqueness of the resources in order to manage processes as a dynamic capability. The presented framework intends to be a guide to managers and researchers to understand how to manage business processes from a resource‐based view to create value to the decision‐makers' perspectives. Copyright © 2014 John Wiley & Sons, Ltd.